Alcohol and tobacco use patterns among heterosexually and homosexually experienced California women - Burgard, Sarah A. (2005)
BACKGROUND: Mounting evidence suggests that lesbians and bisexual women may be at especially elevated risk for the harmful health effects of alcohol and tobacco use. METHODS: We report findings from the California Women’s Health Survey (1998–2000), a large, annual statewide health surveillance survey of California women that in 1998 began to include questions assessing same-gender sexual behavior. RESULTS: Overall, homosexually experienced women are more likely than exclusively heterosexually experienced women to currently smoke and to evidence higher levels of alcohol consumption, both in frequency and quantity. Focusing on age cohorts, the greatest sexual orientation disparity in alcohol use patterns appears clustered among women in the 26–35-year-old group. We also find that recently bisexually active women report higher and riskier alcohol use than women who are exclusively heterosexually active. By contrast, among homosexually experienced women, those who are recently exclusively homosexually active do not show consistent evidence of at-risk patterns of alcohol consumption. DISCUSSION: Findings underscore the importance of considering within-group differences among homosexually experienced women in risk for tobacco and dysfunctional alcohol use.